Typology of Main Errors of Novice Technical Translators (English/Russian) - A. A. Murzakov (Дискурс, 2020)
Introduction. Erratology is a new section of linguistics related to the study of different mistakes. Erratology in the sphere of translation is of particular practical interest since translation errors have a particularly strong effect on areas not even related to linguistics.Methodology and sources. The author analyzed the results of the final test task and developed a typology of the main mistakes of novice technical translators. The classification was not based on a single principle; instead, a comprehensive approach was used. The final classification includes the following types: speech errors, semantic errors, incoherent sentences, terminological errors (incorrect terms and non-unified use of terms), omissions, grammatical errors, misprints, punctuation errors. Since 2014, the author has been conducting e-learning courses on the theory and practice of technical translation for novice and experienced translators who want to improve their skills. Most of the course students were already engaged in translations or planned to start translation activities. For 4 years, 60 people completed most of their homework and the final test task (translation of a technical, medical or legal text (2500 characters with spaces)). The results of the final test task were analyzed and the main types of errors of novice technical translators were identified.Results and discussion. The resulting distribution of the error types is the following: speech errors – 47; semantic errors – 19; incorrect terms – 13; not unified use of terms – 13; omissions – 11; grammatical errors – 7; not unified expression of obligation – 7; misprints – 5; incoherent sentences – 4. The domination of speech errors is caused by a low level of philological literacy of modern Russian society as well as by the removal of proofreaders and editors from the publication process due to cost reduction. Semantic errors are caused by an insufficient level of knowledge in a particular field of knowledge. Other errors are stipulated because of a lack of self-control skills.Conclusion. As a result of the analysis of the test works of novice translators, a practical typology of translation errors was developed. As can be seen from the analyzed examples, all the errors of novice translators can be described using the rule of three “I": inattention, ignorance, inexperience.